Code Switching Used by Judges and Models in Indonesia's Next Top Model in NET TV - Hari Kri Surani; Nur Rosita (English Language and Literature, 2023)
This study aimed to analyze the types, social function, and the construction of speaker’s identity in code switching. This research used mixed (qualitative and quantitative) method by transcribing and analysing the videos to find out the types, social functions, and identity in code switching. The data were utterances uttered by participants in Indonesia’s Next Top Model cycle 2. The result of the study showed there were three types of code switching, intra-sentential switching, inter-sentential switching, and tag switching. The most dominant type was intra-sentential switching with 192 utterances, 41 utterances are inter-sentential switching, and 19 utterances for tag switching. Then five function of code switching found in this research, referential function with 3 utterances, directive function with 15 utterances, expressive function with 37 utterances, phatic function with 13 utterances, and metalinguistic function which most dominant function used by the speaker with 184 utterances. The construction of identity were divided into four categories, classification with 4 occurrences, relational identification with 15 occurrences, physical identification with 8 occurrences, and functionalization with 34 occurrences.